Toward the Origins of the Mariological Interpretation of the Protoevangelium - Madoz, José (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2023)
In recent years, the study of the Mariological interpretation of the Protoevangelium passage, Genesis 3,15, by the Church Fathers has garnered considerable attention. A turning point in theological critique occurred with the publication of a doctoral thesis by L. Drewniak in 1934, which sparked significant debate. Surprisingly restrictive findings from Drewniak's work challenged the belief held by some theologians that "all or nearly all of the Fathers supported a Mariological interpretation of that passage.
Keywords: mariology; protoevangelium